The Media in Scotland - Neil Blain , David Hutchison (Edinburgh University Press, 2008)
The reason we have sought to publish The Media in Scotland is simple enough: although in the past thirty years several books on aspects of the Scottish media have appeared, cinema being particularly well served, there has been no attempt in one volume to cover the entire territory. (It is not false modesty which makes us say that the small volume of essays on the topic which one of us edited in 1978 was much narrower than the present undertaking.) It is desirable that there should be one book which offers readers a survey of as much of the field as possible, and does so in such a way that current concerns and debates are set in their historical contexts. It is also appropriate, with the third Holyrood parliament well into its stride, that the strengths and weaknesses of the devolution settlement in the com - munications area are examined. As several of our contributors note, there is something a little bit lop-sided about cultural policy being devolved while broadcasting and media ownership remain exclusively the domain of Westminster. But however the devolution settlement might be modified, there are certain issues concerning the media which will still need to be addressed, not simply the legislative powers thereon of the Edinburgh parliament. The options open to a small nation with myriad calls on its budget, a nation, too, that is sensitive – some might say hyper-sensitive – about how it is portrayed, are both limited and challenging. Something needs to be said at the outset about the title of the book, which is not perhaps as self-explanatory as might appear. To the average citizen, the media in Scotland do not comprise only those films, newspapers and broadcast programmes produced north of the border. To such a person exposure to, and consumption of, for example, cinema, will involve for the most part American films, with only occasional English or Scottish offerings – let alone those from elsewhere in the world – as part of the mix. Likewise in television, most of us who live in Scotland most of the time watch programmes from south of the border and from the USA. The situation in radio, however, is more complex, and with newspapers the indigenous dailies dominate the Scottish market – or at least they used to. As for the Internet, the click of a mouse has enabled us all to transcend geographical barriers, and often other barriers as well.